2020
DOI: 10.1101/2020.06.15.152033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of Tpm1.8 domains on actin filaments with single molecule resolution

Abstract: Tropomyosins regulate dynamics and functions of the actin cytoskeleton by forming long chains along the two strands of actin filaments that act as gatekeepers for the binding of other actin-binding proteins. The fundamental molecular interactions underlying the binding of tropomyosin to actin are still poorly understood. Using microfluidics and fluorescence microscopy, we observed the binding of fluorescently labelled tropomyosin isoform Tpm1.8 to unlabelled actin filaments in real time. This approach in conju… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…We thus measured the disassembly rates of neonGreen‐Tpm1.8 domains in the presence of G‐actin only (to prevent filament depolymerization). As was reported previously, Tpm1.8 disassembly is asymmetric, faster at the domain boundary located toward the filament barbed end (Bareja et al , 2020). We found that Tpm domains disassembled equally fast from non‐oxidized and oxidized filaments (Fig 3C and D).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…We thus measured the disassembly rates of neonGreen‐Tpm1.8 domains in the presence of G‐actin only (to prevent filament depolymerization). As was reported previously, Tpm1.8 disassembly is asymmetric, faster at the domain boundary located toward the filament barbed end (Bareja et al , 2020). We found that Tpm domains disassembled equally fast from non‐oxidized and oxidized filaments (Fig 3C and D).…”
Section: Resultssupporting
confidence: 81%
“…We recently characterized the dynamics of Tpm1.8 domains. We found that Tpm1.8 saturates the two strands of the actin filaments independently and that the domain assembly and disassembly is asymmetric: faster at the domain border closer to the filament barbed end (Bareja et al , 2020).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Microfluidic devices and coverslips were prepared as described previously 61 . Images were collected on a custom built TIRF microscope described in Bereja et.…”
Section: Methodsmentioning
confidence: 99%
“…al. 61 with a power density of ∼1–3 W cm -2 (measured at the objective with the laser beam normal to the surface of the coverslip. Single particle photobleaching was first performed using purified, pre-assembled DNA origami template and DNA cargo in DNA imaging buffer immobilized on a coverslip to a density of ∼1000 particles per field of view (FOV).…”
Section: Methodsmentioning
confidence: 99%